Analisis Variabel-Variabel Yang Mempengaruhi Motivasi Kerja Pada Koperasi Persatuan Pedagang Kaki Lima Yogyakarta (KPPKLY) - FX Suwarto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This research is conducted on Koperasi Persatuan Pedagang Kaki Lima Jogjakarta (PPKLJ). The objective of this research is to recognize and analyzeL1) work motivation, (2) assesment tothe variable that influence to the work motivation, (3) both the significance and insignificance of the nine variable to the workmotivation, (4) variables which are the most significantÂ to the workmotivation. Quistioner and interview are used to collect data on this research.there are independent variable (X) Consisting of wage (X1),work place (X2), work equipment (X3),work attitute to the job (X4), the attitute to co-workers (X5) trust and responcibility (X6), the needs to develop the ability (X7), the needs to get the best performance (X8); and the dependent variable (Y), which is work motivation. SPS is used to analyze the data on this research. By calculating the data analysis, it is abtained that there are (1) high work motivation on the worker, (2) good worker assesment to variables that influent work motivation, (3) eight variables significantly influence work motivation, (4) the needs variables to get the best performance have the most significant influence to work motivation. The conclusion of the analysis result is that the eight variables exceedingly influence to the work it would be able to develop the worker work motivation, the manager is expected to concern of those eight variables. Particulary the variable of need to get best performance (X8), since it has the most significant influence, there fore the purpose of worker effort continiusly guaranteed.